Temperature in High Temperature SHPB Experiments - 邓志方 谢若泽 颜怡霞 李思忠 黄西成 (Transactions of Tianjin University, 2008)
As an experimental technique, it＇s desired that the temperature in specimen is uniform in high temperature split Hopkinson pressure bar （SHPB） experiments. However, the temperature in specimen decreases and the temperature of bars increases when specimen starts to contact with bars, which induces the nonuniform temperature distribution in specimen, and may result in inac- curacy of experimental results. In this paper, the temperature distributions of specimen and bars in high temperature SHPB experiments were investigated while the specimen was heated alone. Firstly, the temperature history of specimen was measured at different initial temperatures by experiments, then simulation was carried out. Simulation results were consistent with experimental results by adjusting the thermal contact coefficient between specimen and bars. By this way, the thermal contact coefficient and simulation results were validated, and the proper cold contact times of specimen and bars in high temperature SHPB experiments were discussed. Finally, the results were compared with those in references.